Fresno County Counsel Office Holiday Party - Watkins, Howard::::::::: (1985)
Sandy Hill, Georgia York, Nancy Smith (hidden), John Slutter, Floyd Viau, Pamela Stone, Debbie Lucas, Barbara Christiansen, Virginia Avila, Mary Herrick, John Duffy, Peggy Smith, Helen Apodaca